Implementation Of Habituation Program Of Tadarus Al-Qur'an In Love Building Of Al-Quran At Students Of Smp Muhammadiyah 15sedayulawas Brondong Lamongan - Muhammad Hambal (TADARUS, 2018)
Abstract This study aims to delve into the implementation of program habituation of tadarus Qur'an in coaching love of the Qur'an at students of SMP Muhammadiyah 15 SedayulawasBrondongLamongan. This study used a qualitative research, with descriptive approach. The process of data collection was done by using the instrument of observation, interviews and documentation. The data have been collected and analyzedby the collection, reduction, and presentation of data and the conclusion in accordance with the scope of the problem. The results of this study indicated that habituation of tadarus Qur'an program in SMP Muhammadiyah 15 SedayulawasBrondongLamongan is for students to read the Qur'an held every morning before starting the lesson, the program of conditioning tadarus the Qur'an aims to establish thestudent Islamic character that is loving Qur'an more by reading or listening happily. Therefore, this activity becomes a tradition that is deemed suitable for the students in religious activities and as a means of well habituation in daily activities in the realm of religion that led to the approach of the Qur'an. Keywords: Tadarusal-Qur’an, Habituation, Buildinglove of the al-Qur’an